PERFORMA PERTUMBUHAN IKAN NILA (Oreochromis niloticus) YANG DIBERIKAN PAKAN DENGAN PENAMBAHAN SINBIOTIK (Lactobacillus spp. x Ipomoea batatas L.) PADA DOSIS YANG BERBEDA: Growth Performance Of Nile Tilapia (Oreochromis niloticus) Fed A Diet Supplemented With Synbiotics (Lactobacillus Spp. X Ipomoea Batatas L) At Different Doses - Immanuel Kristo Limbong; Ni Nyoman Dian Martini; Alexander Korinus Marantika (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2026)
Tilapia production is greatly influenced by feed as a source of energy and nutrients that support growth, health, survival, and reproduction. The growth rate of fish is closely related to feed quality, so that growth optimization can be achieved through the provision of quality feed. The ingredient that can be used as an alternative for optimizing feed quality is purple sweet potato flour (Ipomoea batatas L.). The purpose of this study was to determine the effect of commercial feed added synbiotics with different doses on the growth rate of tilapia. This study used a complete random design method with 3 treatments, with a maintenance duration of 56 days. Each treatment uses commercial feed, treatment 1 is control, treatment 2 is 1.5% prebiotic and probiotic 2%, treatment 3 is 2% prebiotic and probiotic 2%. The results of the assumption test stated that treatment 3 obtained a significant number as well as the highest score with an absolute weight of 28.59, SGR of 3.32, FER of 78.4, FCR of 1.28. This value illustrates that synergibiotic feed has the potential to improve the quality and quality of feed which leads to the growth rate of tilapia.